2004
DOI: 10.1051/0004-6361:20034542
|View full text |Cite
|
Sign up to set email alerts
|

Phase diversity restoration of sunspot images

Abstract: Abstract. We investigate the dynamics of and the relations between small-scale penumbral and photospheric features near the outer penumbral boundary: penumbral grains (PGs), dark penumbral fibrils, granules, and photospheric G-band bright points. The analysis is based on a 2 h time sequence of a sunspot close to disc center, taken simultaneously in the G-band and in the blue continuum at 450.7 nm. Observations were performed at the Swedish Vacuum Solar Telescope (La Palma) in July 1999. A total of 2564 images … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…One can also mention that, at the disk center, the variation of the number of magnetic bright points which form the photospheric network, varies by no more than 30% through the cycle 24 (Utz et al 2016); this means that such a weak variation of the quiet sun network magnetic field has no detectable effect on the solar granulation observed with HINODE/SOT in the period November 2006-February 2016 Thus, the question of the variation of the solar granulation related to the solar cycle is still open. To solve this issue, the granulation images should be restored from atmospheric seeing (for ground based observations) and corrected for instrumental aberrations like it was done, for example, by Bonet et al (2004) on images taken with the Swedish 1-m telescope in La Palma. In the space, regular in-flight calibrations are recommended for further images restoration, as was done for the IMaX (Imaging Magnetograph eXperiment) instrument onboard the 1-m stratospheric telescope of the SUNRISE mission (Vargas 2009).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One can also mention that, at the disk center, the variation of the number of magnetic bright points which form the photospheric network, varies by no more than 30% through the cycle 24 (Utz et al 2016); this means that such a weak variation of the quiet sun network magnetic field has no detectable effect on the solar granulation observed with HINODE/SOT in the period November 2006-February 2016 Thus, the question of the variation of the solar granulation related to the solar cycle is still open. To solve this issue, the granulation images should be restored from atmospheric seeing (for ground based observations) and corrected for instrumental aberrations like it was done, for example, by Bonet et al (2004) on images taken with the Swedish 1-m telescope in La Palma. In the space, regular in-flight calibrations are recommended for further images restoration, as was done for the IMaX (Imaging Magnetograph eXperiment) instrument onboard the 1-m stratospheric telescope of the SUNRISE mission (Vargas 2009).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Simultaneous observation of MMFs -5in G-band and Ca II K spectral lines showed that MMFs were observed as bright features in both the photosphere and chromosphere (Ryutova et al 1997). Bonet et al (2004Bonet et al ( , 2005 carried out further studies on bright features in G-band and showed that most of them form adjacent to dark penumbral filaments and then move outward from the sunspot at a speed of 0.7 km s −1 . The statistical study by Hagenaar & Shine (2005) showed that MMFs follow preferred paths that were consistent with the moat flows around sunspots.…”
Section: Introductionmentioning
confidence: 99%
“…Via line fitting and with proper modeling, this indirect technique allows us to infer the physical properties of unresolved structures. Second, one gains spatial resolution by directly improving the image quality of the observations, which involves both the optical quality of the instrumentation and the application of image restoration techniques (e.g., Muller 1973aMuller , 1973bBonet et al 1982Bonet et al , 2004Bonet et al , 2005Stachnik et al 1983;Lites et al 1990;Title et al 1993;Sütterlin et al 2001;Scharmer et al 2002;Rimmele 2004). Eventually the two approaches have to be combined when the relevant length scales are comparable to the photon mean-free-path (see, e.g., Sánchez Almeida 2001).…”
Section: Introductionmentioning
confidence: 99%